Υποθαλάσσιες κοιλάδες στη Μεσόγειο και στις ελληνικές θάλασσες - Ζάνταλης, Αλέξανδρος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών, 2018)
Submarine canyons have been the subject of research for along time. Shepard (1972) refers to a study from as early as the late nineteenth century, carried out by Milne (1897), which looked at the instability of canyon floor sediments as a possible cause for the repeated breaking of submarine cables that had been laid across a canyon. However, as a result of the steep terrain, locally enhanced current sand occasional down-canyon flushing events, the initial submarine canyon investigations were extremely challenging, and the number of studies was limited. Acoustic methods had to deal with excessives catter and noise, in-situ instruments were regularly washed away and the coarse canyon thalwegs and rocky walls proved difficult to sample. Direct observations were limited to shallow waters, within reach of divers or early submarines. With the increasing availability of new sampling and surveying technologies (deep-towed acoustic instruments, drop-down video systems, and eventually robotic vehicles), submarine canyon research increased dramatically. Particularly the advent of Remotely Operated Vehicles (ROVs) in many research institutes in the last 10years opened up a new perspective on submarine canyons, allowing a wider community of researchers to access parts of the deep ocean that had been hidden until then. As a result of this increased research effort, our understanding of submarine canyons is gradually growing. A number of individual canyon systems have received considerable attention, but most canyons around the world have not yet been studied, or only to a very limited extend. Further- more, many of the studies carried out so far are focussing on one aspect (geology, geomorphology, sediment dynamics, hydrography, current patterns, mega-, macro-, meio fauna distribution, biogeochemistry…) of a single canyon or canyon system. The time seems right to start putting all those pieces of the jigsaw together, and to start looking at canyons in a more holistic way. To this end, the first International Symposiumon Submarine Canyons was organised in Brest, France in July2012. Canyon research from all over the world was presented, followed by cross-disciplinary discussions and networking. The aim of this thesis is, taking into consideration various studies, to present the submarine canyons morfology and specially around Mediterranean Sea.